A lithium ion imprinting composite membrane with enhanced dipole moment, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611179832.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-08-05
AI Technical Summary
[0007]本发明的目的在于提供一种结合碱蚀-酯化表面改性策略与紫外引发原位聚合技术,在PVDF多孔膜基底上制备锂离子印迹复合膜的新方法,并通过在紫外光引发锂离子印迹聚合过程中引入较大偶极矩的功能单体与选择性配体进行复合,从而增强膜表面的离子-偶极作用力,增强的离子-偶极作用会降低锂离子的脱溶剂化能垒,提高对锂离子的吸附性能,解决了现有锂离子印迹复合膜存在基底界面稳定性差,膜吸附动力单一、亲水性匹配不足,制备周期长,重现性差的技术问题
本发明不仅为高性能锂离子选择性分离膜的开发提供了一种创新、高效的制备路线,也为解决复杂体系中金属离子的高效分离与回收难题提供了新的材料基础和技术参考,具体地:
Smart Images

Figure CN122665500B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of imprinted film technology, specifically to a dipole moment-enhanced lithium-ion imprinted composite film, its preparation method, and its application. Background Technology
[0002] The sustainable supply and efficient recycling of lithium—a key raw material for lithium-ion batteries—has become a major issue in the energy and environmental fields. Achieving highly selective enrichment and separation of lithium ions from complex secondary resources such as salt lake brines, lithium extraction mother liquor from ores, and spent lithium-ion batteries is crucial for ensuring lithium resource security and promoting the development of a circular economy. Traditional separation technologies, such as precipitation and solvent extraction, often suffer from long processes, limited selectivity, and potential environmental pollution. Therefore, developing separation materials and technologies that combine high selectivity, high permeability flux, excellent stability, and environmental friendliness has significant scientific and practical value.
[0003] Molecular imprinting is an advanced material preparation strategy capable of constructing predetermined specific recognition sites. Lithium-ion imprinted polymers are created by copolymerizing lithium ions as template molecules with functional monomers and crosslinking agents to form a three-dimensional network structure. Removing the template leaves imprinted cavities in the polymer matrix that are highly complementary to the template ions in size, shape, and functional group arrangement. These materials exhibit hole-matching specific recognition capabilities for target ions. However, conventional bulk or particulate lithium-ion imprinted polymers often face limitations in separation applications, such as high mass transfer resistance, low site accessibility, and difficulty in integration into continuous flow separation devices. Constructing imprinted layers on porous membrane substrates with high-flux characteristics to form lithium-ion imprinted composite membranes is an effective way to solve these problems. It combines the specific recognition of imprinted sites with the high efficiency of the membrane separation process, achieving integrated adsorption and separation.
[0004] Polyvinylidene fluoride (PVDF) membranes are considered ideal substrate materials for separation membranes due to their excellent chemical stability, mechanical strength, film-forming properties, and solvent resistance. However, the strong inertness of the PVDF membrane surface and the lack of active functional groups that can interact with lithium ions limit its direct use for ion imprinting. Therefore, surface modification of PVDF membranes to introduce copolymerizable or coordinated active sites is a prerequisite for constructing high-performance lithium-ion imprinted membranes. Currently, most PVDF-based imprinted membranes use physical coating or polydopamine (PDA) interlayers. Under extreme operating conditions of strong acids / bases / high solvent concentrations, the imprinted polymer layer is prone to swelling, peeling, or detachment from the porous substrate, resulting in a limited service life. Furthermore, the strong hydrophobicity of the PVDF substrate makes it difficult to match with the hydrophilic imprinted layer, even with the use of a PDA interlayer, which is difficult to completely solve, affecting the mass transfer efficiency of the membrane in aqueous solutions.
[0005] Existing crown ether imprinted membranes, such as 12-crown-4-ether (12C4) imprinted membranes, suffer from low dipole moments due to the highly symmetrical structure of the 12C4 structure. This results in low electrostatic potential of the oxygen atoms, allowing adsorption only through size-matching effects (hole-ion geometric matching). They cannot utilize ion-dipole interactions to provide additional adsorption driving forces. Furthermore, the high desolvation energy barrier of lithium ions limits adsorption efficiency and capacity. In addition, lithium ions need to remove surrounding bound water before entering the crown ether cavity, leading to low hydrophilicity in lithium-ion imprinted membranes (MIIMs).
[0006] Membrane adsorption technology holds promise for the specific and selective adsorption of particular ions, which is crucial for resource development and recycling, as well as the advancement of new energy technologies. While fabricating ion-adsorption membranes capable of achieving specific selective ion adsorption is vital, it undoubtedly presents a significant technological challenge. Ion-dipole interactions are intermolecular forces between ions and polar molecules with dipole moments, arising from the uneven charge distribution within the polar molecules. However, the mechanism by which changes in dipole moment affect the selective adsorption of ions remains unclear. Summary of the Invention
[0007] The purpose of this invention is to provide a novel method for preparing lithium-ion imprinted composite membranes on PVDF porous membrane substrates by combining an alkaline etching-esterification surface modification strategy with UV-initiated in-situ polymerization technology. This method enhances the ion-dipole interaction on the membrane surface by introducing functional monomers with larger dipole moments and selective ligands during UV-initiated lithium-ion imprinting polymerization. The enhanced ion-dipole interaction lowers the desolvation energy barrier of lithium ions, improving their adsorption performance. This solves the technical problems of existing lithium-ion imprinted composite membranes, such as poor substrate interface stability, a single membrane adsorption motive force, insufficient hydrophilicity matching, long preparation cycle, and poor reproducibility.
[0008] The present invention achieves the above objectives through the following technical solutions: As a first aspect of the present invention, a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film is provided, comprising the following steps: (1) The polyvinylidene fluoride membrane was modified by alkaline etching-esterification to obtain a functionalized PVDF membrane with methacrylic acid and carbon-carbon double bonds grafted on the surface. (2) Under nitrogen protection, lithium-ion template, 12-crown-4-ether, methacrylic acid, crosslinking agent and photoinitiator are mixed and pre-assembled in an organic solvent to obtain lithium-ion imprinted prepolymer solution; (3) The prepolymer solution is coated on the surface of the functionalized PVDF membrane. Under nitrogen protection, free radical polymerization is initiated by ultraviolet light irradiation, so that methacrylic acid, crosslinking agent and 12-crown-4-ether copolymerize on the membrane surface to form a three-dimensional crosslinking network. The methacrylic acid is covalently anchored to the carbon-carbon double bonds grafted on the membrane surface to form a lithium-ion imprinted polymer layer. The methacrylic acid and 12-crown-4-ether are combined to form lithium-ion recognition sites with enhanced dipole moment. (4) Elute the template ions and dry to obtain a lithium-ion imprinted composite film with enhanced dipole moment.
[0009] As a further optimization of the present invention, in step (1), the alkaline etching-esterification surface modification includes: immersing the PVDF film in an aqueous solution of sodium hydroxide or sodium bicarbonate with a concentration of 1-4 mol / L, soaking it at 20-60°C for 0.5-2 hours for alkaline etching, and then immersing it in a methacrylic acid solution with a concentration of 1-3 mol / L, soaking it at room temperature for 30-60 minutes for esterification grafting.
[0010] As a further optimization of the present invention, in step (2), the lithium-ion template is anhydrous lithium chloride, and the amount used is 0.2-0.5g; the organic solvent is anhydrous methanol or anhydrous acetonitrile.
[0011] As a further optimization of the present invention, in step (2), the amount of 12-crown-4-ether used is 0.5 to 3 mmol.
[0012] As a further optimization of the present invention, in step (2), the crosslinking agent is ethylene glycol dimethacrylate, and the amount used is 0.5 to 2 mmol; the amount of methacrylic acid is 0.1 to 0.3 mL.
[0013] As a further optimization of the present invention, in step (2), the photoinitiator is 2-hydroxy-2-methylphenylacetone or 1-hydroxycyclohexylphenyl ketone, and the amount used is 0.1 to 0.3 mL.
[0014] As a further optimization of the present invention, in step (3), the ultraviolet irradiation time is 10 to 60 minutes.
[0015] As a further optimization of the present invention, in step (4), the elution is to immerse the membrane in a hydrochloric acid solution with a concentration of 1 mol / L, and to clean it by oscillation or ultrasonication at room temperature for 30 to 60 minutes, repeating 2 to 3 times; the drying is to dry in a vacuum drying oven at 50°C for 12 to 24 hours.
[0016] As a second aspect of the present invention, a dipole moment-enhanced lithium-ion imprinted composite film is also provided, which is prepared by the method described in any of the above-mentioned methods.
[0017] As a third aspect of the present invention, an application of the dipole moment-enhanced lithium-ion imprinted composite membrane as described above in the selective adsorption and separation of lithium ions is also provided.
[0018] The beneficial effects of this invention are as follows: This invention not only provides an innovative and efficient preparation route for the development of high-performance lithium-ion selective separation membranes, but also offers a new material basis and technical reference for solving the problem of efficient separation and recovery of metal ions in complex systems. Specifically: (1) The present invention adopts an alkaline etching-esterification strategy, which covalently grafts MAA onto the PVDF surface through ester bonds, and then uses UV-initiated polymerization to covalently anchor the double bonds of MAA and PVDF surface, forming a stable three-layer structure of PVDF-MAA graft layer-imprinted polymer layer. The covalent bond connection is much stronger than physical adhesion, which fundamentally solves the problem of imprinted layer peeling and shedding, and significantly improves interface stability.
[0019] (2) In this invention, after combining MAA with crown ether ligands, the bulk symmetry of the crown ether is regulated, the dipole moment is increased, and the polarity is enhanced. Density functional theory (DFT) simulation calculations confirm that after polymerization, the electrostatic potential of both MAA and oxygen atoms in 12C4 increases to varying degrees, and the ion-dipole interaction is significantly enhanced, providing an additional electrostatic driving force for lithium ion adsorption. The enhanced ion-dipole interaction also lowers the desolvation energy barrier of lithium ions, making it easier for lithium ions to remove bound water and enter the crown ether cavity. DFT simulation calculations show that the binding energy of lithium ions with the imprinted polymer is much lower than that with water, indicating that lithium ions can be stably adsorbed in the imprinted system, thereby simultaneously improving the adsorption efficiency and capacity of the membrane.
[0020] (3) The present invention introduces abundant hydrophilic functional groups such as carboxyl groups through MAA, and the enhanced dipole moment increases the polarity of the membrane surface and significantly improves the hydrophilicity. Water flux test shows that the water flux gradually increases after alkaline etching-esterification, which is beneficial for the transfer of lithium ions to the membrane surface in aqueous solution.
[0021] (4) The present invention optimizes the adsorption / desorption kinetics through the reversible ion-dipole interaction between MAA and lithium ions, thereby greatly improving the reusability performance.
[0022] (5) The preparation cycle of the present invention is greatly shortened, the parameters of each step are controllable, the process has good reproducibility, and it is conducive to large-scale production. Attached Figure Description
[0023] Figure 1 SEM images of the PVDF substrate membrane and MIIM membrane surfaces provided by this invention; Figure 2 Analysis of the MIIM membrane adsorption kinetics model (a) and adsorption isotherm model (b) provided for this invention; Figure 3 Fourier transform infrared spectroscopy analysis of the MIIM film provided by this invention; Figure 4 DFT simulation dipole moment analysis (a) and binding energy analysis (b) of MIIM film provided for this invention; Figure 5 The present invention provides DFT calculations of the electrostatic potential changes of oxygen atoms in polymers and monomer ligands; wherein, (a) is a quantification diagram of the electrostatic potential changes of oxygen atoms; and (b) are the ESP distribution diagrams of MAA, 12C4, and MAA-12C4 complexes, respectively. Figure 6 Water flux test results of the PVDF substrate membrane (a), NPVDF membrane (b), MPVDF membrane (c), and MIIM membrane (d) provided for this invention; Figure 7 Thermogravimetric analysis results of the MIIM membrane prepared in Example 1 of this invention; Figure 8 Cyclic performance of the MIIM membrane prepared in Example 1 of this invention; Figure 9 The adsorption capacity of lithium ions on lithium-ion imprinted composite membranes prepared by changing the MAA concentration in Examples 1 to 4 of this invention is shown in the figure. Figure 10 The adsorption capacity of lithium ions of the lithium-ion imprinted composite membranes prepared by changing the amount of 12C4 ether added in Examples 5 to 7 of this invention is shown in the diagram. Figure 11 Adsorption capacity of lithium ions of lithium-ion imprinted composite membranes prepared by varying the amount of crosslinking agent EDGMA in Examples 1, 8 to 10 of the present invention; Figure 12 Adsorption capacity of lithium ions of lithium-ion imprinted composite membranes prepared by changing the ultraviolet irradiation time in Examples 1, 11 to 13 of the present invention; Figure 13 The lithium-ion imprinted composite membranes prepared for comparative examples 1(a), 2(b), and 3(c) of this invention are compared with the adsorption capacity of lithium ions in Example 1. Figure 14 The lithium-ion imprinted composite membranes prepared in Comparative Examples 4(a), 5(b), 6(c) and 7(d) provided for this invention have the same adsorption capacity for lithium ions as those in Comparative Example 1. Figure 15 The graph shows the adsorption capacity of the lithium-ion imprinted composite film prepared in Comparative Example 8 compared to that in Example 1. Detailed Implementation
[0024] The present application will now be described in further detail with reference to the accompanying drawings. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.
[0025] The present invention achieves the following technical solution through at least one typical embodiment: A method for preparing a dipole moment-enhanced lithium-ion imprinted composite film includes the following steps: S1, Pretreatment of PVDF base film Polyvinylidene fluoride (PVDF) flat sheet membrane or hollow fiber membrane is used as the base membrane. It is immersed in a sodium hydroxide aqueous solution or sodium bicarbonate aqueous solution with a concentration of 1-4 mol / L and soaked at 20-60℃ for 0.5-2 hours to carry out surface alkaline etching treatment, so that hydrogen fluoride is defluorinated on the surface of PVDF membrane to generate carbon-carbon double bonds and active functional groups such as hydroxyl and carboxyl groups. The PVDF base membrane that has undergone alkaline etching pretreatment is denoted as NPVDF. NPVDF is immersed in a MAA solution with a concentration of 1-3 mol / L and soaked at room temperature for 30-60 min. This allows the carboxyl groups of MAA to undergo an esterification reaction with the hydroxyl groups on the NPVDF membrane surface, thus grafting them onto the membrane surface. After the grafting reaction, the membrane is washed with methanol or ethanol and then with deionized water to obtain a MAA-functionalized membrane, denoted as MPVDF.
[0026] S2, Preparation of lithium-ion imprinted prepolymer solution Prepare the lithium-ion imprinted prepolymer solution under light-protected conditions according to the following steps: (1) Weigh 0.2-0.5g of anhydrous lithium chloride (LiCl) as template ion, dissolve it in 10-50mL of anhydrous methanol or anhydrous acetonitrile, stir until completely dissolved, and obtain a solution; (2) Add 0.5–3 mmol of 12-crown-4-ether to the above solution and stir continuously at 25°C for 1–2 hours to allow Li to react. + It fully pre-assembles with crown ether molecules through ion-dipole interactions to form a host-guest complex; (3) Add 0.5-2 mmol of crosslinking agent and 0.1-0.3 mL of methacrylic acid (98%, MAA) to the pre-assembled mixture in sequence. The crosslinking agent is ethylene glycol dimethacrylate (EGDMA). Continue stirring for 10-20 min to make it evenly mixed. (4) Add 0.1 to 0.3 mL of photoinitiator to the above system. The photoinitiator is 2-hydroxy-2-methylphenylacetone or 1-hydroxycyclohexylphenyl ketone. Stir and dissolve under nitrogen protection. (5) The above mixed solution is continuously purged with high-purity nitrogen for 15-25 minutes to remove dissolved oxygen in the system and avoid the inhibitory effect of oxygen on subsequent free radical polymerization, so as to obtain lithium ion imprinted prepolymerization solution. S3, Photo-initiated surface imprinting polymerization Spread the MPVDF flat on a clean glass plate or polytetrafluoroethylene film-forming mold. Use a pipette to take an appropriate amount of lithium ion imprinting prepolymerization solution and evenly coat or drop it onto the film surface, ensuring that the solution completely wets the film surface. The mold is transferred to a UV curing device and irradiated with a 365nm UV lamp under a nitrogen atmosphere for 10–60 minutes to initiate a free radical polymerization reaction. This causes the functional monomers, crosslinking agents, and crown ether molecules to copolymerize on the membrane surface to form a three-dimensional crosslinked network. Simultaneously, the functional monomers are covalently anchored to the double bonds grafted onto the PVDF surface, thereby forming a stable lithium-ion imprinted polymer layer on the membrane surface.
[0027] S4. Template elution and drying After polymerization, the membrane is removed and immersed in a 1 mol / L hydrochloric acid solution, and then shaken or ultrasonically cleaned at room temperature for 30–60 min. This process is repeated 2–3 times to wash away the Li in the imprint layer. + Template ions. The membrane was repeatedly washed with deionized water until the eluent was neutral, and the Li in the eluent was detected by atomic absorption spectrometry or inductively coupled plasma atomic emission spectrometry. + Concentration, until Li is undetectable. + The template was confirmed to have been completely removed. The eluted membrane was placed in a vacuum drying oven and dried at 50°C for 12–24 h to obtain a dipole moment-enhanced lithium-ion imprinted composite membrane, denoted as MIIM.
[0028] The MIIM film prepared by the above method has a three-layer composite structure, consisting of PVDF, MAA grafted layer and lithium-ion imprinted polymer layer from top to bottom. The shape can be regular rectangle or circle, with uniform thickness, smooth edges, and a total thickness of 50μm to 300μm.
[0029] The working principle of the MIIM membrane is based on the size matching effect. The diameter of the crown ether molecule is highly matched with the diameter of the dehydrated lithium ion. Other ions cannot enter the cavity due to size mismatch. When the lithium ion approaches the cavity, the ion generates a strong ion-dipole interaction with the crown ether-MAA complex, which causes the lithium ion to lose its bound water and enter the crown ether cavity, thus achieving adsorption.
[0030] The MIIM membrane working process involves cutting the prepared lithium-ion imprinted composite membrane to a suitable size and weighing it. The membrane is then immersed in a lithium-containing solution and subjected to constant temperature shaking or static placement; the adsorption time is typically 1–3 hours. After adsorption saturation, the membrane is removed, and its surface is rinsed with dilute acid for reuse.
[0031] The present invention will be described below through specific embodiments. It should be noted that the specific embodiments below are for illustrative purposes only and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods that do not specifically describe conditions or steps are conventional methods, and the reagents and materials used can be obtained commercially.
[0032] Example 1
[0033] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, including the following steps: S1, Basement membrane pretreatment Polyvinylidene fluoride flat sheet membrane was used as the base membrane and immersed in a 3 mol / L sodium hydroxide aqueous solution for 1 hour at room temperature to perform surface alkaline etching treatment, so that hydrogen fluoride was defluorinated on the PVDF surface to generate carbon-carbon double bonds and active functional groups such as hydroxyl and carboxyl groups. The PVDF membrane after surface alkaline etching treatment is denoted as NPVDF. The NPVDF was immersed in a 2 mol / L MAA solution and soaked at room temperature for 30 min to allow MAA to bind to the membrane surface through esterification. The membrane was then washed with methanol and deionized water to obtain the MAA-functionalized membrane, denoted as MPVDF.
[0034] S2, Preparation of lithium-ion imprinted prepolymer solution Prepare the prepolymer solution under light-protected conditions according to the following steps: (1) Weigh 0.3g of anhydrous lithium chloride as the template ion, dissolve it in 30mL of anhydrous methanol and stir until completely dissolved to obtain a solution; (2) Add 1.5 mmol of 12-crown-4-ether to the above solution and stir continuously at 25°C for 2 hours to allow Li to react. + It is fully pre-assembled with 12-crown-4-ether through ion-dipole interactions to form a host-guest complex; (3) Add 1 mmol of crosslinking agent EGDMA and 0.1 mL of methacrylic acid to the pre-assembled mixture in sequence, and continue stirring for 10 min to make it evenly mixed; (4) Add 0.1 mL of 2-hydroxy-2-methylphenylacetone to the above system and stir to dissolve under nitrogen protection; (5) The above mixed solution is continuously purged with high-purity nitrogen (99.9999%) for 15 min to remove dissolved oxygen in the system and avoid the inhibitory effect of oxygen on subsequent free radical polymerization, so as to obtain lithium ion imprinted prepolymer solution.
[0035] S3, Photo-initiated surface imprinting polymerization Spread the MPVDF flat on a clean polytetrafluoroethylene film-forming mold. Use a pipette to take an appropriate amount of lithium ion imprinting prepolymerization solution and coat or drop it evenly onto the film surface, ensuring that the solution completely wets the film surface. The mold is transferred to a UV curing device and irradiated with a 365nm UV lamp under a nitrogen atmosphere for 15 minutes to initiate a free radical polymerization reaction. This causes MAA, crosslinking agent, and 12-crown-4-ether to copolymerize on the membrane surface to form a three-dimensional crosslinked network. At the same time, the carbon-carbon double bonds grafted onto the PVDF surface by MAA undergo covalent anchoring, thereby forming a stable lithium-ion imprinted polymer layer on the membrane surface.
[0036] S4. Template elution and drying After polymerization, the membrane was removed and immersed in a 1 mol / L hydrochloric acid solution, and washed with shaking at room temperature for 30 min. This process was repeated three times to elute the Li in the imprint layer. + Template ions. The membrane was repeatedly washed with deionized water until the eluent was neutral, and the Li in the eluent was detected by atomic absorption spectrometry or inductively coupled plasma atomic emission spectrometry. + Concentration, until Li is undetectable. + The template was confirmed to have been completely removed. The eluted membrane was placed in a vacuum drying oven and dried at 50°C for 12 hours to obtain the dipole moment-enhanced lithium-ion imprinted composite membrane, denoted as MIIM.
[0037] The MIIM prepared in Example 1 was tested for the following items: (1) The polymer morphology on the surfaces of MIIM and PVDF was observed using SEM. For example... Figure 1 As shown, the MIIM membrane surface has an additional thin polymer layer compared to the PVDF membrane surface. This layer is a lithium-ion imprinted polymer layer, which proves the successful synthesis of the lithium-ion imprinted composite membrane.
[0038] (2) The adsorption performance of MIIM was determined using ICP-AES. Specifically, after MIIM was placed in a lithium ion solution with a lithium ion concentration of 200 mg / L for 2 h, three parallel samples were set up for each group. The lithium ion concentration before and after adsorption was tested using ICP-AES, and the adsorption capacity (Q) was calculated according to the following formula. e ): ;
[0039] In this formula, C0 and C e The values represent the lithium ion concentrations before and after adsorption, respectively; V represents the solution volume; and m represents the membrane mass.
[0040] As a comparison, the present invention also prepared an imprinted film without imprinting treatment, the steps of which are as follows: S1, Basement membrane pretreatment Polyvinylidene fluoride flat sheet membrane was used as the base membrane and immersed in a 3 mol / L sodium hydroxide aqueous solution for 1 hour at room temperature to perform surface alkaline etching treatment, so that hydrogen fluoride was defluorinated on the PVDF surface to generate carbon-carbon double bonds and active functional groups such as hydroxyl and carboxyl groups. The PVDF membrane after surface alkaline etching treatment is denoted as NPVDF. The NPVDF was immersed in a 2 mol / L MAA solution and soaked at room temperature for 30 min to allow MAA to bind to the membrane surface through esterification. The membrane was then washed with methanol and deionized water to obtain the MAA-functionalized membrane, denoted as MPVDF.
[0041] S2, Preparation of prepolymerization solution Prepare the prepolymer solution under light-protected conditions according to the following steps: (1) Add 1.5 mmol of 12-crown-4-ether to 30 mL of anhydrous methanol solution and stir continuously at 25 °C for 2 h to form a host-guest complex; (2) Add 1 mmol of crosslinking agent EGDMA and 0.1 mL of methacrylic acid to the pre-assembled mixture in sequence, and continue stirring for 10 min to make it evenly mixed; (3) Add 0.1 mL of 2-hydroxy-2-methylphenylacetone to the above system and stir to dissolve under nitrogen protection; (4) The above mixed solution is continuously purged with high-purity nitrogen (99.9999%) for 15 min to remove dissolved oxygen in the system and avoid the inhibitory effect of oxygen on subsequent free radical polymerization, thus obtaining a prepolymerization solution.
[0042] S3, Photo-initiated surface imprinting polymerization Spread the MPVDF evenly on a clean polytetrafluoroethylene film-forming mold. Use a pipette to take an appropriate amount of prepolymerization solution and evenly coat or drop it onto the film surface, ensuring that the solution completely wets the film surface. The mold is transferred to a UV curing device and irradiated with a 365nm UV lamp under a nitrogen atmosphere for 15 minutes to initiate a free radical polymerization reaction. This causes MAA, crosslinking agent, and crown ether molecules to copolymerize on the membrane surface to form a three-dimensional crosslinked network. At the same time, the carbon-carbon double bonds grafted onto the PVDF surface by MAA undergo covalent anchoring, thereby forming a stable imprinted polymer layer on the membrane surface.
[0043] S4, Drying After polymerization, the membrane is removed and repeatedly washed with deionized water until the washing solution is neutral. The washed membrane is then placed in a vacuum drying oven and dried at 50°C for 12 hours to obtain an untreated imprinted membrane, denoted as MNIIM.
[0044] according to Figure 2 (a) and Figure 2 (b) Based on the adsorption test data of MIIM, the following conclusions were drawn from the analysis of adsorption kinetics model and adsorption isotherm model: By comparing the quasi-first-order dynamic model (R 2 =0.987) and the quasi-second-order dynamic model (R 2 =0.99) Fitted R 2 Value, MIIM film for Li + The adsorption of Li is more consistent with the quasi-second-order kinetic model, indicating that Li + Imprinted sites on the membrane are formed by chemical chelation ( Figure 2 (a)); By comparing the Langmuir model (R 2 =0.978) and the Freundlich model (R 2 =0.937) Fitted R 2 The value further reflects Li + The adsorption behavior on MIIM is at a uniform monomolecular level. Figure 2 (b)).
[0045] (3) Fourier transform infrared spectroscopy was used to determine ( Figure 3 MIIM surface functional groups were used to observe whether the film polymerization was successful. Figure 3 It can be seen from the presence of -OH and C=C in NPVDF, indicating that the NaOH alkaline etching was successful; in MIIM, C=O and OCO are present at 1720 cm⁻¹. -1 and 1237cm -1 The appearance of a peak value indicates successful aggregation.
[0046] (4) DFT simulation: Theoretical calculations were performed using the Gaussian 16 package. The structures of the studied molecules and their complexes were fully optimized at the B3LYP-D3BJ / 6-31G(d) theoretical level. The vibrational frequencies of the optimized structures were also calculated at the same level. By verifying that all vibrational frequencies were positive, the local energy minima corresponding to each structure on the potential energy surface were confirmed.
[0047] The dipole moment of the molecule was calculated at the theoretical level of B3LYP-D3BJ / 6-311+G(d). The optimized Li + The interaction energy (ΔE) of the complex was calculated at the theoretical level of B3LYP-D3BJ / 6-311+G(d). ΔE is defined as the difference between the complex energy and the sum of the monomer energies, obtained by the formula ΔE=E(AB)-E(A)-E(B). Color-filled isosurface plots were generated using the Visual Molecular Dynamics (VMD) program to visualize the molecular electrostatic potential (MESP).
[0048] DFT simulations show that MAA and crown ethers enhance polarity by modulating the bulk symmetry of the crown ether, thereby promoting Li + Dehydration with water ( Figure 4 (a)); Figure 4 (b) As shown in the figure, the binding energy of lithium ions with water is much lower than that with the imprinted polymer, indicating that lithium ions can be stably adsorbed in the imprinted system. This plays a positive role in the adsorption of lithium ions from the aqueous solution to the membrane surface. MAA and crown ether provide abundant electron donors and nucleophilic sites, improving the adsorption capacity of lithium ions on the membrane. + Adsorption.
[0049] The electrostatic potentials of oxygen atoms in MAA-O1 and MAA-O2, oxygen atoms in 12C4-O, and oxygen atoms in MAA-12C4-O (1-5) after polymerization were calculated using DFT simulations. Figure 5 (a) It can be seen that after polymerization, the electrostatic potential of oxygen atoms in MAA and 12C4 in the MAA-12C4 complex increases to varying degrees, the ion-dipole interaction is enhanced, and the adsorption of lithium ions is improved. Figure 5 (b) shows the electrostatic potential distribution of MAA, 12C4, and the MAA-12C4 complex.
[0050] (5) Water flux test The water flux of PVDF substrate membrane, NPVDF membrane, MPVDF membrane, and lithium-ion imprinted composite membrane (MIIM) was tested using a flat sheet membrane apparatus. Specifically, a cross-flow filtration system with a permeation area of approximately 7 cm² was used. 2 A flat sheet membrane (1.5 cm radius) was used to evaluate its permeation performance. The operating system was thoroughly cleaned and rinsed before the filtration experiments. Initially, the membrane was filtered for 2 hours at an operating pressure of 4 bar using deionized water as the feed solution to ensure membrane stability. Then, performance evaluation was performed at 1 bar (unless otherwise specified), with water flux tested at time points of 0.5 h, 1.0 h, 1.5 h, and 2 h.
[0051] Water flux is calculated using the following formula: ;
[0052] Where V represents the permeation volume (L) and A represents the effective membrane area (cm²). 2 ), t represents the filtration time (h), and Δp represents the operating pressure (bar).
[0053] Figure 6 (a)-(d) are the 2-hour water permeability performance diagrams for PVDF, NPVDF, MPVDF, and MIIM, respectively. Figure 6 Observations show that alkaline etching increases the pore size and water flux of the PVDF membrane. Grafting MAA introduces the hydrophilic functional group -COOH, which further improves the water flux. Finally, the lithium-ion imprinted membrane has a polymer layer loaded on its surface, and the surface roughness is increased, which reduces the hydrophilicity and thus decreases the water flux.
[0054] (6) Thermogravimetric analysis (VGA) was used to investigate the thermal stability of the polymer and its proportion in the total membrane. Specifically, VGA was performed under a nitrogen atmosphere, with the temperature increased to 800°C at a rate of 10°C / min. The stability of the polymer on the membrane surface and the proportion of each component in the total membrane were determined based on the weight change with temperature. Figure 7 Observations show that thermogravimetric analysis of the membrane under completely dried conditions revealed that the polymer on the membrane surface began to decompose at 130°C. This polymer accounted for approximately 4% of the total membrane mass, indicating that the prepared lithium-ion imprinted membrane has excellent thermal stability.
[0055] (7) Cyclic performance of lithium-ion imprinted composite membrane The prepared MIIM was immersed in a lithium ion solution with a concentration of 200 mg / L for 2 hours, then removed and the current concentration of the solution was measured. The adsorbed lithium ions on the MIIM were then eluted using 1 mol / L HCl. This cycle was repeated nine times. Figure 8 Observations show that during the adsorption-elution-adsorption cycle, the adsorption capacity of the MIIM membrane decreased by only about 7% after the 9th cycle, indicating that the membrane has excellent cycle stability.
[0056] Example 2
[0057] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, which differs from Example 1 in that S1, substrate film pretreatment: In this embodiment, NPVDF is immersed in a 1 mol / L methacrylic acid (MAA) solution, and the other steps and parameters are the same as in Example 1.
[0058] Example 3
[0059] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, which differs from Example 1 in that S1, substrate film pretreatment: In this embodiment, NPVDF is immersed in a 1.5 mol / L methacrylic acid (MAA) solution, and the other steps and parameters are the same as in Example 1.
[0060] Example 4
[0061] The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film provided in this embodiment differs from that in Example 1 in that S1, substrate film pretreatment: NPVDF is immersed in a 2.5 mol / L methacrylic acid (MAA) solution, while the other steps and parameters are the same as in Example 1.
[0062] At room temperature, 0.02 g of the membranes prepared in Examples 1 to 4 were immersed in 50 ml of lithium ion solutions with lithium ion concentrations of 50, 100, 200, and 300 mg / L (pH=7) for 2 h, respectively. Three parallel groups were set up, and the solutions after adsorption were taken for ICP-AES testing.
[0063] Figure 9 This is a graph showing the adsorption capacity of lithium-ion imprinted composite membranes prepared by varying MAA concentrations in Examples 1 to 4. Figure 9 It can be seen that the optimal concentration of MAA used for grafting is 2 mol / L.
[0064] Example 5
[0065] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, which differs from Example 1 in that S2, the preparation of the lithium-ion imprinted prepolymer solution: In this embodiment, the amount of 12C4 added is 0.5 mmol, and the other steps and parameters are the same as in Example 1.
[0066] Example 6
[0067] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, which differs from Example 1 in that S2, the preparation of the lithium-ion imprinted prepolymer solution: In this embodiment, the amount of 12C4 added is 1 mmol, and the other steps and parameters are the same as in Example 1.
[0068] Example 7
[0069] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film. The difference between this method and Example 1 is that in S2, the preparation of the lithium-ion imprinted prepolymer solution is as follows: the amount of 12C4 added is 2 mmol. All other steps and parameters are the same as in Example 1.
[0070] At room temperature, 0.02 g of the membranes prepared in Examples 1 and 5-7 were immersed in 50 ml of lithium ion solutions with lithium ion concentrations of 50, 100, 200, and 300 mg / L (pH=7) for 2 h, respectively. Three parallel groups were set up, and the solutions after adsorption were taken for ICP-AES testing.
[0071] Figure 10This is a graph showing the adsorption capacity of lithium-ion imprinted composite membranes prepared by varying the amount of 12C4 added in Examples 1 and 5-7. Figure 10 It can be seen that the optimal amount of 12C4 added is 1.5 mmol.
[0072] Example 8
[0073] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, which differs from Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymer solution is as follows: In this embodiment, the amount of crosslinking agent EDGMA added is 0.5 mmol, and the other steps and parameters are the same as in Example 1.
[0074] Example 9
[0075] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, which differs from Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymer solution is as follows: In this embodiment, the amount of crosslinking agent EDGMA added is 1.5 mmol, and the other steps and parameters are the same as in Example 1.
[0076] Example 10
[0077] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, which differs from Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymer solution is as follows: In this embodiment, the amount of crosslinking agent EDGMA added is 2 mmol, and the other steps and parameters are the same as in Example 1.
[0078] At room temperature, 0.02 g of the membranes prepared in Examples 1 and 8-10 were immersed in 50 ml of lithium ion solutions with lithium ion concentrations of 50, 100, 200, and 300 mg / L (pH=7) for 2 h, respectively. Three parallel groups were set up, and the solutions after adsorption were taken for ICP-AES testing.
[0079] Figure 11 This is a graph showing the adsorption capacity of lithium-ion imprinted composite membranes prepared in Examples 1 and 8-10 by varying the amount of crosslinking agent EDGMA. Figure 11 It can be seen that the optimal addition amount of the crosslinking agent EDGMA is 1.5 mmol.
[0080] Example 11
[0081] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film. The difference between this method and Example 1 is that in step S3, photo-initiated surface imprinting polymerization, the ultraviolet irradiation time is shortened to 10 min in this embodiment, while the other steps and parameters are the same as in Example 1.
[0082] Example 12
[0083] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film. The difference between this embodiment and Example 1 is that in step S3, photo-initiated surface imprinting polymerization: in this embodiment, the ultraviolet irradiation time is extended to 20 min, while the other steps and parameters are the same as in Example 1.
[0084] Example 13
[0085] This embodiment provides a method for preparing a dipole moment-enhanced lithium-ion imprinted composite film. The difference between this embodiment and Example 1 is that in step S3, photo-initiated surface imprinting polymerization, the ultraviolet irradiation time is extended to 25 min, while the other steps and parameters are the same as in Example 1.
[0086] At room temperature, 0.02 g of the membranes prepared in Examples 1 and 11-13 were immersed in 50 ml of lithium ion solutions with lithium ion concentrations of 50, 100, 200, and 300 mg / L (pH=7) for 2 h, respectively. Three parallel groups were set up, and the solutions after adsorption were taken for ICP-AES testing.
[0087] Figure 12 This is a graph showing the adsorption capacity of lithium-ion imprinted composite films prepared by varying the UV irradiation time in Examples 1 and 11-13. Figure 12 It can be seen that the optimal ultraviolet light exposure time is 15 minutes.
[0088] Comparative Example 1 The method for preparing a lithium-ion imprinted composite membrane provided in this comparative example differs from Example 1 only in S1, the pretreatment of the substrate membrane: In this comparative example, the PVDF membrane is immersed in a dopamine (PDA) solution with a concentration of 2 g / L for 2 hours, and then rinsed three times with ultrapure water. All other steps and parameters are the same as in Example 1.
[0089] Comparative Example 2 The method for preparing a lithium-ion imprinted composite film provided in this comparative example differs from that in Example 1 in that this comparative example does not perform S1 and substrate pretreatment, while the other steps and parameters are the same as in Example 1.
[0090] Comparative Example 3 The method for preparing a lithium-ion imprinted composite film provided in this comparative example differs from that in Example 1 in that, in S1, the substrate film pretreatment is performed only by surface alkaline etching, without MAA grafting. The other steps and parameters are the same as in Example 1.
[0091] At room temperature, 0.02 g of the membranes prepared in Comparative Examples 1-3 were immersed in 50 ml of lithium ion solutions with lithium ion concentrations of 50, 100, 200, and 300 mg / L (pH=7) for 2 h, respectively. Three parallel groups were set up, and the solutions after adsorption were taken for ICP-AES testing.
[0092] Figure 13 The graph shows the adsorption capacity of lithium ions in the lithium-ion imprinted composite films prepared in Comparative Examples 1-3 compared to that in Example 1. Figure 13 (a) It can be seen that, in Comparative Example 1, the PDA layer, while providing abundant active sites (catechol, amino groups, etc.), cannot replace the carboxyl groups of MAA to form strong hydrogen bonds with 12C4. The interaction between PDA and 12C4 is mainly weak π-π stacking or van der Waals forces, which cannot effectively induce electron cloud polarization of 12C4. This results in a lower adsorption capacity of the prepared membrane compared to the MIIM prepared after alkaline etching-esterification.
[0093] from Figure 13 (b) It can be seen that Comparative Example 2 did not undergo alkaline etching-esterification pretreatment of the substrate membrane. The original PVDF surface had no active groups that could form covalent bonds with MAA (no hydroxyl groups, no carboxyl groups, no double bonds). MAA could not be anchored to the membrane surface, and the imprinted layer was only physically embedded on the PVDF. The imprinted layer was easily detached during elution and adsorption, resulting in an adsorption capacity of the prepared membrane that was lower than that of MIIM.
[0094] from Figure 13 (c) It can be seen that the substrate membrane of Comparative Example 3 only underwent surface alkaline etching treatment without MAA grafting. Although alkaline etching can generate a small number of carboxyl groups on the PVDF surface, the carboxyl group density is extremely low, far from sufficient to form a sufficient dipole-enhanced microenvironment around 12C4. The ion-dipole interaction is weak, resulting in an adsorption capacity of the prepared membrane that is lower than that of MIIM.
[0095] Comparative Example 4 The method for preparing a lithium-ion imprinted composite membrane provided in this comparative example differs from that in Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymerization solution is as follows: In this comparative example, MAA is not added when preparing the lithium-ion imprinted prepolymerization solution, and the other steps and parameters are the same as in Example 1. The prepared membrane is designated as IIM.
[0096] Comparative Example 5 The method for preparing a lithium-ion imprinted composite membrane provided in this comparative example differs from that in Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymer solution is as follows: In this comparative example, MAA is replaced with acrylic acid (AA) when preparing the lithium-ion imprinted prepolymer solution. All other steps and parameters are the same as in Example 1. The prepared membrane is designated as AA-IIM.
[0097] Comparative Example 6 The method for preparing a lithium-ion imprinted composite membrane provided in this comparative example differs from that in Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymer solution is as follows: In this comparative example, MAA is replaced with acrylamide when preparing the lithium-ion imprinted prepolymer solution, and the other steps and parameters are the same as in Example 1. The prepared membrane is designated as acrylamide-IIM.
[0098] Comparative Example 7 The method for preparing a lithium-ion imprinted composite membrane provided in this comparative example differs from that in Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymerization solution is as follows: In this comparative example, MAA is replaced with 4-vinylpyridine (4VP) when preparing the lithium-ion imprinted prepolymerization solution. All other steps and parameters are the same as in Example 1. The prepared membrane is designated as acrylamide 4VP-IIM.
[0099] At room temperature, 0.02 g of the membranes prepared in Comparative Examples 4-7 were immersed in 50 ml of lithium ion solutions with lithium ion concentrations of 50, 100, 200, and 300 mg / L (pH=7) for 2 h, respectively. Three parallel groups were set up, and the solutions after adsorption were taken for ICP-AES testing.
[0100] Figure 14 The graph shows the adsorption capacity of lithium ions in the lithium-ion imprinted composite films prepared in Comparative Examples 4-7 compared to that in Example 1. Figure 14 (a) It can be seen that when preparing the lithium-ion imprinted prepolymerization solution in Comparative Example 4, no MAA was added, and no free MAA participated in the Li-ion prepolymerization solution. + -12C4 pre-assembly. Although there are grafted MAA on the membrane surface, their density is limited and they cannot fully form a pre-assembled complex with 12C4 in solution. The ion-dipole interaction is weak, electrostatic attraction is dominant, the lithium ion desolvation efficiency is low, and the adsorption capacity is also low.
[0101] from Figure 14 (b) It can be seen that when MAA was replaced with AA in the preparation of the lithium-ion imprinted prepolymerization solution in Comparative Example 5, AA also contains a carboxyl group and can form hydrogen bonds with 12C4. However, AA lacks α-methyl (-CH3), and the directionality and strength of its hydrogen bonds with 12C4 are different from those of MAA. The absence of α-methyl makes the dipole moment enhancement of the AA-12C4 complex less than that of the MAA-12C4 complex, and its effect on changing the dipole moment of 12C4 ether is less than that of MAA, resulting in the adsorption capacity of the prepared membrane being lower than that of MIIM.
[0102] from Figure 14(c) It can be seen that when MAA was replaced with acrylamide in the preparation of the lithium-ion imprinted prepolymerization solution in Comparative Example 6, AM contains amide groups (-CONH2). Although it can also form hydrogen bonds, the strength and directionality of its hydrogen bond donor (NH) and acceptor (C=O) are different from those of the carboxyl group. The polarization ability of the amide group to 12C4 ether oxygen is much weaker than that of the carboxyl group in MAA, resulting in a lower adsorption capacity of the prepared membrane than MIIM.
[0103] from Figure 14 (d) It can be seen that when MAA was replaced with 4-vinylpyridine in the preparation of the lithium-ion imprinted prepolymerization solution in Comparative Example 7, the interaction between the pyridine ring of 4-vinylpyridine and the 12C4 ether was not as strong as that of MAA. 4-VP contains nitrogen atoms on the pyridine ring, and its interaction with metal ions is mainly through coordination bonds rather than hydrogen bonds. The lack of effective hydrogen bond interaction between 4-VP and 12C4 makes it impossible to induce electron cloud polarization of 12C4. The dipole enhancement effect is almost zero, resulting in an adsorption capacity of the prepared membrane that is lower than that of MIIM.
[0104] Comparative Example 8 The method for preparing a lithium-ion imprinted composite film provided in this comparative example differs from that in Example 1 in that, in step S2, the preparation of the lithium-ion imprinted prepolymerization solution is as follows: In this comparative example, the 12-crown 4-ether was replaced with benzo15-crown 5-ether when preparing the lithium-ion imprinted prepolymer solution, and all other steps and parameters were the same as in Example 1.
[0105] At room temperature, 0.02 g of the membrane prepared in Comparative Example 8 was immersed in 50 ml of lithium ion solutions with lithium ion concentrations of 50, 100, 200, and 300 mg / L (pH=7) for 2 h. Three parallel groups were set up, and the solutions after adsorption were taken for ICP-AES testing.
[0106] Figure 15 The graph shows the adsorption capacity of the lithium-ion imprinted composite film prepared in Comparative Example 8 compared to that in Example 1. Figure 15 It can be seen that the rigidity of the benzene ring structure of the modified benzo
[15] crown[5]ether is enhanced, and the conformational adaptability when forming hydrogen bonds with MAA is not as good as that of 12C4. The dipole enhancement effect may be different. No change in dipole moment was generated between MAA and the membrane, and the ion-dipole interaction is weak, which makes the adsorption capacity of the prepared membrane lower than that of MIIM.
[0107] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a dipole moment-enhanced lithium-ion imprinted composite film, characterized in that, Includes the following steps: (1) The polyvinylidene fluoride membrane was modified by alkaline etching-esterification to obtain a functionalized PVDF membrane with methacrylic acid and carbon-carbon double bonds grafted on the surface. (2) Under nitrogen protection, lithium-ion template, 12-crown-4-ether, methacrylic acid, crosslinking agent and photoinitiator are mixed and pre-assembled in an organic solvent to obtain lithium-ion imprinted prepolymer solution; (3) The prepolymer solution is coated on the surface of the functionalized PVDF membrane. Under nitrogen protection, free radical polymerization is initiated by ultraviolet light irradiation, so that methacrylic acid, crosslinking agent and 12-crown-4-ether copolymerize on the membrane surface to form a three-dimensional crosslinking network. The methacrylic acid is covalently anchored to the carbon-carbon double bonds grafted on the membrane surface to form a lithium-ion imprinted polymer layer. The methacrylic acid and 12-crown-4-ether are combined to form lithium-ion recognition sites with enhanced dipole moment. (4) Elute the template ions and dry to obtain a lithium-ion imprinted composite film with enhanced dipole moment.
2. The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film according to claim 1, characterized in that, In step (1), the alkaline etching-esterification surface modification includes: immersing the PVDF film in a sodium hydroxide aqueous solution or sodium bicarbonate aqueous solution with a concentration of 1~4 mol / L, soaking it at 20~60℃ for 0.5~2h for alkaline etching, and then immersing it in a methacrylic acid solution with a concentration of 1~3 mol / L, soaking it at room temperature for 30~60min for esterification grafting.
3. The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film according to claim 1, characterized in that, In step (2), the lithium-ion template is anhydrous lithium chloride, and the amount used is 0.2-0.5g; The organic solvent is anhydrous methanol or anhydrous acetonitrile.
4. The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film according to claim 1, characterized in that, In step (2), the amount of 12-crown-4-ether used is 0.5 to 3 mmol.
5. The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film according to claim 1, characterized in that, In step (2), the crosslinking agent is ethylene glycol dimethacrylate, and the amount used is 0.5 to 2 mmol; the amount of methacrylic acid is 0.1 to 0.3 mL.
6. The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film according to claim 1, characterized in that, In step (2), the photoinitiator is 2-hydroxy-2-methylphenylacetone or 1-hydroxycyclohexylphenyl ketone, and the amount used is 0.1 to 0.3 mL.
7. The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film according to claim 1, characterized in that, In step (3), the ultraviolet irradiation time is 10 to 60 minutes.
8. The method for preparing a dipole moment-enhanced lithium-ion imprinted composite film according to claim 1, characterized in that, In step (4), the elution involves immersing the membrane in a 1 mol / L hydrochloric acid solution and oscillating or ultrasonically cleaning it at room temperature for 30–60 min, repeating 2–3 times; the drying involves drying it in a vacuum drying oven at 50°C for 12–24 h.
9. A dipole moment-enhanced lithium-ion imprinted composite film, characterized in that, It is prepared by the method described in any one of claims 1 to 8.
10. The application of the dipole moment-enhanced lithium-ion imprinted composite membrane as described in claim 9 in the selective adsorption and separation of lithium ions.
Citation Information
Patent Citations
Preparation method of high-adsorption-capacity lithium ion imprinted nano composite membrane
CN111632500A
Preparation method and application of multi-layer polyelectrolyte nanofiltration membrane based on 15-crown-5 ether as lithium ion imprinting channel
CN117323833A